Characteristics and In-Hospital Outcomes of Patients With Non–ST-Segment Elevation Myocardial Infarction and Chronic Kidney Disease Undergoing Percutaneous Coronary Intervention - Hanna, Elias B. (JACC Cardiovasc Interv, 2011)
OBJECTIVES: This study sought to evaluate the characteristics, therapies, and outcomes of patients with chronic kidney disease (CKD) presenting with non–ST-segment elevation myocardial infarction (NSTEMI) and managed with percutaneous coronary intervention (PCI). This speci?c population has not been evaluated previously. BACKGROUND: Among patients with acute coronary syndrome, the presence of renal dysfunction is associated with an increased risk of death and major bleeding. METHODS: We examined data on 40,074 NSTEMI patients managed with PCI who were captured by the ACTION (Acute Coronary Treatment and Intervention Outcomes Network) registry. Patients were divided according to baseline renal function in 4 groups: no CKD and CKD stages 3, 4, and 5. RESULTS: Overall, 31.1% (n = 12,045) of patients with NSTEMI undergoing PCI had CKD. Compared with patients with normal renal function, CKD patients managed with PCI had signi?cantly more history of myocardial infarction, heart failure, and more 3-vessel coronary artery disease. They received fewer antithrombotic therapies but were treated more frequently with bivalirudin. In addition, they had significantly higher rates of inhospital mortality and major bleeding. CKD stage 4 was associated with the highest risk of adverse events relative to no CKD. The multivariable adjusted odds ratios of in-hospital mortality for CKD stages 3, 4, and 5 relative to no CKD were 2.0, 2.8, and 2.6, respectively (global p value <0.0001), and the analogous adjusted odds ratios of major bleeding were 1.5, 2.8, and 1.8, respectively (global p value <0.0001). CONCLUSIONS: CKD patients presenting with NSTEMI and managed with PCI have more comorbidities and receive guideline-recommended therapies less frequently than do patients without CKD. CKD is strongly associated with in-hospital mortality and bleeding in NSTEMI patients undergoing PCI.